The role of control at border posts in the Northwest Province in the prevention of transboundry animal disease spread in South Africa - Van Vuuren, Moritz (University of Pretoria, 2013)
Dissertation (MSc (Veterinary Tropical Diseases))--University of Pretoria, 2012.